Dakwahtaiment Televisi Lokal (Tinjauan Kritis Atas Komesialisasi Dakwah JTV Surabaya) - Salman Zahidi; Muhammad Zainudin Alansori (Universitas Nahdlatul Ulama Surabaya, 2019)
Da'wah is an influencing process, so its effectiveness needs to be supported by the presence of the media. However, the existence of the media in turn is like a double-edged knife. On the one hand it provides greater convenience and affordability, but the media also has the consequence of the potential to make religion an economic commodity. This last impact will be revealed in this article. By conducting field studies through qualitative methods, it was successful to find important conclusions, namely: 1) The da'wah process carried out by JTV was designed using several supporting instruments. Like music and also the MC who must have a high sense of humor. 2) commercialization features of JTV da'wah include; commodification of content, audience, intrinsic and extrinsic 3) The factors that become primary determinations in carrying out the entertainment process of da'wah programs on JTV are; 1) attracting public interest, 2) raising ratting and share, 3) provoking advertisers